2010
DOI: 10.4103/0973-6247.67037
|View full text |Cite
|
Sign up to set email alerts
|

Pre-donation deferral of blood donors in South Indian set-up: An analysis

Abstract: Background:It is well known that quite a large number of apparently healthy donors are not able to donate blood successfully because of varied reasons.Aim:We want to analyze the rate and various reasons for deferrals.Materials and Methods:A retrospective analysis of records of the donors, for 3 years, from January 2005 to December 2007 was done, in order to find out the rate and causes of deferral in four categories of age groups, both in male and female, in our Transfusion Medicine Centre, Bangalore, India.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
42
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 12 publications
22
42
6
1
Order By: Relevance
“…Males outnumbered females almost twenty times. Preponderance of male blood donors has also been reported by several other authors [5][6][7][8][9][10][11][12][13][14][15]. Alfouzan [16] in his study reported high blood donation attitude score and significantly higher blood donation knowledge in males than females, which could be the probable reason of male preponderance in our study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Males outnumbered females almost twenty times. Preponderance of male blood donors has also been reported by several other authors [5][6][7][8][9][10][11][12][13][14][15]. Alfouzan [16] in his study reported high blood donation attitude score and significantly higher blood donation knowledge in males than females, which could be the probable reason of male preponderance in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the donors deferred in this study were in the age group 18-30 years (55.5%). Almost similar age related demographic profile was described in the studies under taken by other authors [5][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Several studies have reported a similar deferral rate (5.20%) by Unnikrishnan et al [3], (6%) by Sundar et al [4], and (5.6%) by Rabeya et al [5]. Some studies have even had a higher deferral rate of (16.4%) Chaudhary et al [6], (35.6%) Charles et al [7].…”
Section: Discussionmentioning
confidence: 75%
“…The deferred 858 cases were categorized into temporary constituting (58.04%) with 95% CI: 54.66%-61.37% and permanent (41.96%) with 95% CI: 38.63%-45.34% in (Table 3, 4,5). Among the 498 temporarily deferral cases, anemia was the number one cause of deferral constituting (15.66%), followed by medications (11.65%), fever (9.44%) as shown in (Table3).…”
Section: Resultsmentioning
confidence: 99%